PENGARUH DIVERSIFIKASI TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Pardede, Theo; Lumban Gaol, Romasi (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to analyze the effect of diversification on company performance in manufacturing companies listed on the IDX. The population of this study are manufacturing companies in the basic and chemical industry sectors listed on the IDX in 2015-2019. The sample in this study was obtained by means of purposive sampling, with a total sample of 15 companies. Data collection techniques using documentation techniques. The analytical method used is a simple linear regression equation. The test results show that the diversification variable has a tcount of -1.549 < from ttable which is 1.99254 with a significance level of 0.124 > 0.05, it is concluded that diversification has a negative and insignificant effect on company performance in manufacturing companies listed on the IDX in 2015- 2019. Keywords: Diversification, Company Performance